Open questions on the functional biology of the yolk granules during embryo development. Issue 2 (12th January 2022) - Ramos, Isabela; Machado, Ednildo; Masuda, Hatisaburo; Gomes, Fabio
Abstract: Biogenesis and consumption of the yolk are well‐conserved aspects of the reproductive biology in oviparous species. Most egg‐laying animals accumulate yolk proteins within the oocytes thus creating the source of nutrients and energy that will feed embryo development. Yolk accumulation drives the generation of a highly specialized oocyte cytoplasm with maternal mRNAs, ribosomes, mitochondria, and, mainly, a set of organelles collectively referred to as yolk granules (Ygs). Following fertilization, the Ygs are involved in regulated mechanisms of yolk degradation to fuel the anabolic metabolism of the growing embryo. Thus, yolk accumulation and degradation are essential processes that allow successful development in many species. Nevertheless, the molecular machinery and mechanisms dedicated to the programmed yolk mobilization throughout development are still enigmatic and remain mostly unexplored. Moreover, while the Ygs functional biology as a nutritional source for the embryo has been acknowledged, several reports have suggested that Ygs cargoes and functions go far beyond yolk storage. Evidence of the role of Ygs in gene expression, microbiota harboring, and paracrine signaling has been proposed. In this study, we summarize the current knowledge of the Ygs functional biology pointing to open questions and where further investigation is needed. Abstract : The functional biology of the yolk granules.